THE CORRELATION OF BUZZ MARKETING EXPOSURE OF EVENTSMGID AND EDUCATIONAL LEVEL OF FOLLOWER WITH FOLLOWER DECISION TO COME TO EVENTSMGID MEDIA PARTNER - Maulana, Ahmad; Naryoso, S.Sos, M.Si, Agus (Interaksi Online, 2017)
Holding an event is one of marketing communication tool that conducted by a company, institution, or organization to achieve certain goals. In the implementation, to reach the desired targets of visitors, event organizer can invite buzzer media partner as third party to promote their event, including in Semarang city. One of buzzer media partner form that exist in Semarang is EVENTSMGID. EVENTSMGID have done media buzzing well to attract consumers. However, in reality there are some events which are cooperate and trusting marketing strategy through social media to EVENTSMGID could not reach the visitors that they want so they loss.Therefore, this research aim to know whether buzz marketing of EVENTSMGID is correlated with follower decision to come to EVENTSMGID Media Partner. Beside buzz marketing exposure, this research also examining the correlation of Educational Level of Follower with follower decision to come to EVENTSMGID Media Partner. The theory used in this research is Elaboration Likelihood Theory. This is explanatory research that will explaining cause and effect among variables. Sample of this research are active followers of EVENTSMGID during one last year. The amount of respondents are 96 peoples took based on purposive sampling. Data analysis used in this research is Kendall Tau-B analysis. The results of this research showed that the exposure of buzz marketing has positively correlated with follower decision to come to EVENTSMGID Media Partner and the educational level of follower has negatively correlated with follower decision to come to EVENTSMGID Media Partner.